The Experimental Composition Improvisation Continua Model: A Tool for Musical Analysis - Spence, Alister (Frontiers in Psychology, 2021)
Among improvisers and composers today there is a resurgence of interest in experimental music (EM) practices that welcome contingency; engaging with unforeseen circumstances as an essential component of the music-making process, and a means to sonic discovery. I propose the Experimental Composition Improvisation Continua (ECIC) as a model with which to better understand these experimental musical works. The historical Experimental Music movement of the 1950s and 60s is briefly revisited, and the jazz tradition included as an essential protagonist; both being important historical movements leading to the formulation of ideas around contingent musical practices. The ECIC model is outlined as providing a means to observe the interactions and continua between composition and improvisation on the one hand and more or less experimentally conceived music on the other. This model is applied as an investigative and comparative tool to three distinctive works in order to illuminate the presence or otherwise of various experimental interactions within them. The works are: “Spiral Staircase” – a composition by written by Satoko Fujii in late 2007, John Cage’s 4′33″, and a performance of “My Favorite Things” by the John Coltrane Quartet. Further possible applications of the ECIC are suggested in the conclusion.